METHODOLOGY AND CRITERIA OF THE BASIS FOR STUDYING THE FUNCTION OF TECHNICAL COMPLEXES IN THE CREATION OF CONSTRUCTION OBJECTS - Gorbatyuk, Ievgenii (SWorld-Ger Conference proceedings, 2025)
This work studies the process of optimal energy consumption with the help of engineering complexes and studies the target transfer of energy to the working environment when creating defense, industrial, private and infrastructure facilities. It is propose